Pacifism and war on international political thought and the construction of a human right and fundamental to Peace - Vieira, André LuizValim [UNESP] (Universidad Nacional Autonoma de Mexico, 2021)
This article aims to study pacifism and peace research in relation to the political theory of international relations that consider war as an object of study and primordial analysis throughout modern thought. Using historical and bibliographical research we intend to identify pacifism and peace as a human and fundamental right in the international order and in the internal legal order. Our goal, therefore, is to understand pacifist thinking in international law and how peace can represent the logic of relations between nations in the 21st century and how it means a fundamental right of protection in the domestic and international order.
Pacifisme et guerre dans la pensée politique internationale et construction d’un droit humain et fondamental à la paix
Pacifismo e guerra no pensamento político internacional e a construção de um direito humano e fundamental à paz
Keywords: Human rights; Pacifism; Peace; War